Representasi Cinta dalam Lirik Lagu Khotya, Al-Harbein dan Metl Al-Amira Karya Bessan Ismail (Semiotika Roland Barthes): Representations of Love in the Lyrics of Bessan Ismail's Songs Khotya, Al-Harbein, and Metl Al-Amira (Roland Barthes's Semiotics) - Azahra Dwi Putri Ru; Rohanda Rohanda; Resa Restu Pauji (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2026)
This research is motivated by listeners' limited understanding of the metaphorical meaning in Arabic song lyrics, which are rich in symbolism and figurative language and are often treated as aesthetic works rather than explored in depth. This research aims to examine the representation of love in the lyrics of Bessan Ismail's songs Khotya, Al-Harbein, and Metl Al-Amira through Roland Barthes' semiotic approach. The method used is a descriptive qualitative method, with literature review techniques and purposive sampling as the basis for data collection. The analysis is carried out through three stages of meaning, namely denotation, connotation, and myth, by dissecting lexical meanings through the Arabic dictionary Al-Mu'jam Al-Wasith and referring to the concept of fragments in the book A Lover's Discourse. The results show that love is represented as a complex cultural ideology through five main mythical patterns: the sacredness of the lover, inner emptiness, total surrender, the beauty of wounds, and eternal love. The figurative language in the lyrics functions as a sign system that produces layered meanings while constructing the myth of love as the center of meaning in life, universally ideologized. Furthermore, Bessan Ismail's work demonstrates a harmonious blend of classical Arabic literary aesthetics and contemporary musical nuances, deepening the meaning and strengthening the perspective on depicting love. Theoretically, this research contributes to broadening the understanding of how song lyrics can naturalize certain ideologies through linguistic and symbolic sign systems, ultimately influencing the listener's perspective on emotional reality.